Nitrogen and Phosphorus Retranslocation of Leaves and Stemwood in a Mature Eucalyptus Forest Exposed to 5 Years of Elevated CO2 - Crous, Kristine Y.; Wujeska-Klause, Agnieszka; Jiang, Mingkai; Medlyn, Belinda E.; Ellsworth, David S. (Frontiers in Plant Science, 2019)
Elevated CO2 affects C cycling processes which in turn can influence the nitrogen (N) and phosphorus (P) concentrations of plant tissues. Given differences in how N and P are used by plants, we asked if their stoichiometry in leaves and wood was maintained or altered in a long-term elevated CO2 experiment in a mature Eucalyptus forest on a low P soil (EucFACE). We measured N and P concentrations in green leaves at different ages at the top of mature trees across six years including five years in elevated CO2. N and P concentrations in green and senesced leaves and wood were determined to evaluate both spatial and temporal variation of leaf N and P concentrations, including the N and P retranslocation in leaves and wood. Leaf P concentrations were 32% lower in old mature leaves compared to newly flushed leaves with no effect of elevated CO2 on leaf P. By contrast, elevated CO2 significantly decreased leaf N concentrations in newly-flushed leaves but this effect disappeared as leaves matured. As such, newly-flushed leaves had 9% lower N:P ratios in elevated CO2 and N:P ratios were not different in mature green leaves (CO2 by Age effect, P = 0.02). Over time, leaf N and P concentrations in the upper canopy slightly declined in both CO2 treatments compared to before the start of the experiment. P retranslocation in leaves was 50%, almost double that of N retranslocation (29%), indicating that this site was P-limited and that P retranslocation was an important mechanism in this ecosystem to retain P in plants. As P-limited trees tend to store relatively more N than P, we found an increased N:P ratio in sapwood in response to elevated CO2 (P < 0.01), implying N accumulation in live wood. The flexible stoichiometric ratios we observed can have important implications for how plants adjust to variable environmental conditions including climate change. Hence, variable nutrient stoichiometry should be accounted for in large-scale Earth Systems models invoking biogeochemical processes.